2022
DOI: 10.3390/ma16010276
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of New Generations of Monolithic, Multi-Layered Zirconia

Abstract: New monolithic multi-layered zirconia restorations are gaining popularity due to their excellent aesthetic properties. However, current knowledge of these newest multi-layer ceramics in terms of mechanical properties is scarce. Three monolithic, multi-layered zirconia materials (Katana, Kuraray Noritake, Japan) were selected for comparison: High Translucent Multi-layered zirconia (HTML), Super Translucent Multi-layered zirconia (STML) and Ultra Translucent Multi-layered zirconia (UTML). Fifteen specimens per g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Importantly, this phenomenon was not observed in zirconia ceramics of uniform composition. In a study conducted by Bruhnke et al [49], the researchers investigated the possible differences in mechanical properties, specifically in terms of flexural strength, Vickers hardness, and fracture toughness, among the layers in a blank of zirconia ceramic of uniform composition. The study concluded that there were no statistically significant differences in mechanical properties observed among the layers in the blank.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this phenomenon was not observed in zirconia ceramics of uniform composition. In a study conducted by Bruhnke et al [49], the researchers investigated the possible differences in mechanical properties, specifically in terms of flexural strength, Vickers hardness, and fracture toughness, among the layers in a blank of zirconia ceramic of uniform composition. The study concluded that there were no statistically significant differences in mechanical properties observed among the layers in the blank.…”
Section: Discussionmentioning
confidence: 99%
“…Translucent Monolithic, Multi-Layered Zirconia: Matching Esthetics with Strength Amar Bhochhibhoya 1 1 Assistant Professor, Department of Prosthodontics, T.U. Teaching Hospital, Institute of Medicine, Maharajgunj, Kathmandu, Nepal.…”
Section: Editorialmentioning
confidence: 99%
“…Tetragonal stabilized polycrystalline zirconia (TZP: tetragonal zirconia polycrystal) is doped with 3 mol% yttrium oxide (3Y-TZP). 1 The opaque appearance of zirconia is a key challenge in obtaining optimum esthetics. These restorations are typically veneered with a weak glassy phase ceramic to mask the opaque appearance.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The improvement of zirconia materials has continued, and it has showed promise in terms of enhanced properties. 6 A common problem of ceramics layered upon a coping is the high rate of chipping. Monolithic zirconia is a more recently offered option to PFM and zirconia-ceramic prosthesis.…”
Section: Introductionmentioning
confidence: 99%